Mobility and maternal position during childbirth in Tanzania: an exploratory study at four government hospitals - Smith Helen; Mlay Rose; Lugina Helen (BMC, 2004)
Abstract Background Emerging research evidence suggests a potential benefit in being upright in the first stage of labour and a systematic review of trials suggests both benefits and harmful effects associated with being upright in the second stage of labour. Implementing evidence-based obstetric care in African countries with scarce resources is particularly challenging, and requires an understanding of the cumulative nature of science and commitment to applying the most up to date evidence to clinical decisions. In this study, we documented current practice rates, explored the barriers and opportunities to implementing these procedures from the provider perspective, and documented women's preferences and satisfaction with care. Methods This was an exploratory study using quantitative and qualitative methods. Practice rates were determined by exit interviews with a consecutive sample of postnatal women. Provider views were explored using semi-structured interviews (with doctors and traditional birth attendants) and focus group discussions (with midwives). The study was conducted at four government hospitals, two in Dar es Salaam and two in the neighbouring Coast region, Tanzania. Main outcome measures Practice rates for mobility during labour and delivery position; women's experiences, preferences and views about the care provided; and provider views of current practice and barriers and opportunities to evidence-based obstetric practice. Results Across all study sites more women were mobile at home (15.0%) than in the labour ward (2.9%), but movement was quite restricted at home before women were admitted to labour ward (51.6% chose to rest with little movement). Supine position for delivery was used routinely at all four hospitals; this was consistent with women's preferred choice of position, although very few women are aware of other positions. Qualitative findings suggest obstetricians and midwives favoured confining to bed during the first stage of labour, and supine position for delivery. Conclusions The barriers to change appear to be complicated and require providers to want to change, and women to be informed of alternative positions during the first stage of labour and delivery. We believe that highlighting the gap between actual practice and current evidence provides a platform for dialogue with providers to evaluate the threats and opportunities for changing practice.